Applied math for water plant operators - workbook - Price, Joanne K. ([S.l.] : CRC Press, 1991)
This workbook is a companion to Applied Math for Water Plant Operators (ISBN: 9780877628743) and part of the Applied Math for Water Plant Operators Set (ISBN: 9781566769884). It contains self-teaching guides for all water treatment calculations, skill checks, hundreds of worked examples, and practice problems.